Sulfide-induced dissimilatory nitrate reduction to ammonia in anaerobic freshwater sediments - Brunet, R.C.; Garcia-Gil, L.J.
Different reduced sulfur compounds (H ., S, FeS, S,O:- > were tested as electron donors for dissimilatory nitrate reduction in nitrate-amended sediment slurries. Only-in the free sulfide-enriched slurries was nitrate appreciably reduced to ammonia (0.30 pmol NHl/ymol NO;), with concomitant oxidation of sulfide to So (0.55 pmol S'/pmol S*-). The initial concentration of free sulfide appears as a factor determining the type of nitrate reduction. At extremely low concentrations of free S'- (metal sulfides)nitrate was reduced via denitrification whereas at higher S*- concentrations, dissimilatory nitrate reduction to ammonia (DNRA)and incomplete denitrification to gaseous nitrogen oxides took place. Sulfide inhibition of NO- and N,O- reductases is proposed as being responsible for the driving part of the electron flow from S'- to NH:.
Keywords: SEDIMENT; DENITRIFICATION; DISSIMILATORY NITRATE REDUCTION TO AMMONIA; SULFIDE; FERROUS SULFIDE; THIOSULFATE